Population dynamics and survival of the nematode Ditylenchus destructor on groundnut (Arachis hypogaea) - Basson, Selmare (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. Agric.) -- University of Stellenbosch, 1991.